Computer algebra in scientific computing : 18th International Workshop, CASC 2016, Bucharest, Romania, September 19-23, 2016, Proceedings /: 18th International Workshop, CASC 2016, Bucharest, Romania, September 19-23, 2016, Proceedings. (2016) - Unknown
No abstract available